Species lists of plants - Shoop, M., author; Wasser, C. H., author; Engel A., author; Hazlett, Dan, author; Augustine, David, author; Martyn, Trace, author; Milchunas, Daniel, author; Stapp, Paul, author; Kaplan, Nicole, author; Lindquist, Mark, author (Colorado State University. Libraries, 2007)
Working list of plants used by the SGS-LTER Program on the Central Plains Experimental Range, Nunn, Colorado.
Keywords: long term ecological research; shortgrass steppe; grassland ecology; Central Plains Experimental Range; Pawnee National Grassland